FRANKL’S TRAGIC OPTIMISM: : ANALYSIS OF THE REPORT OF A ONCOLOGICAL PATIENT - Couto Assis, Mariana (Health and Society, 2021)
The article analyzes the tragic triad, brought by Frankl on Logotherapy, on the true story of cancer patient’s last days, in the book “Chasing the daylight”, by Eugene O’Kelly, main author and protagonist. It was performed a non-systematic review of literature produced in the approach about the subject. The analysis emphasizes the positive attitude towards the components of the triad – pain, guilt and death – as an adequate response to the life’s teasers, and we can turn them into constructive personal changes. It is, then, the triad optimistic, for being opportunity to update and potential growth.